Analisis Tingkat Relevansi Kurikulum Program Studi Pendidikan Teknik Bangunan dengan SMK Program Keahlian - Riansyah Putra; Liana Atika; Mena Fadilia Lukman; Naufal Tinov; Rachmat Mulyana (Departement of Mathematics Education, 2024)
This research aims to determine the relevance level of the curriculum of the Building Engineering Education Program at Universitas Negeri Medan (UNIMED) to the Learning Outcomes of the Construction and Property Engineering Program in the Merdeka Curriculum at Vocational High Schools (SMK). The objects of this research are the curriculum documents of the Building Engineering Education Program and the Learning Outcomes documents of the Construction and Property Engineering Program. This research uses a quantitative descriptive research method with the following stages: data collection, data reduction, data presentation, data verification, and conclusion drawing. The data collection techniques used are literature review, documentation, and interviews. The obtained data is analyzed by assessing the percentage of each competency or learning element of the Vocational High School (SMK) Construction and Property Engineering Program, and then the results are categorized according to the relevance level categories. The results show that the curriculum of the Building Engineering Education Program at Unimed is relevant to the competencies of the Vocational High School (SMK) Construction and Property Engineering Program, with a relevance level of 92,30%.